A New Approach for Dental Bleaching Using Violet Light With or Without the Use of Whitening Gel: Study of Bleaching Effectiveness - Gallinari, M. O. [UNESP]; Fagundes, Ticiane Cestari [UNESP]; Silva, L. M. [UNESP]; Almeida Souza, M. B. de [UNESP]; Barboza, A. C. S. [UNESP]; Briso, André Luiz Fraga [UNESP] (Operative Dentistry Inc, 2019)
The objective of this study was to evaluate the effectiveness of violet light-emitting diodes (LEDs) in dental bleaching treatment when used in conjunction with bleaching gels containing different concentrations of hydrogen peroxide (HP). Here, 90 bovine teeth (n=15) were randomly assigned to the following groups: GI, placebo without light; GII, 35% HP without light; GIII, 17.5% HP without light; GIV, placebo with violet LED; GV, 35% HP with violet LED; and GVI, 17.5% HP with violet LEDs. Three bleaching sessions of 45 minutes were conducted; 21 cycles involving one minute of irradiation by violet LEDs with 30-second intervals were performed during each session of bleaching (GIV, GV, and GVI). Color changes (Delta E, Delta L, Delta a, and Delta b) were analyzed using a visible ultraviolet light spectrophotometer 7 days after each bleaching session. The mean Delta E, Delta L, Delta a, and Delta b values were compared between groups by analysis of variance and Tukey tests, with a significance level of 5%. The groups treated with 35% HP had higher Delta E and Delta L and lower Delta b values, regardless of whether violet light was used. The group that received only violet LED differed from the control group in terms of Delta E, and the group treated with 17.5% HP and violet LED presented higher Delta E values than the group treated with 17.5% HP only. Thus, violet light did not influence bleaching efficacy when using 35% HP, but when used in conjunction with 17.5% HP, it increased the bleaching efficacy. Moreover, use of the violet LED only also prompted a bleaching effect, although it was less marked.